Informal Consequences of Budget Institutions in the US Congress. Issue 4 (11th May 2016) - Clarke, Andrew J.; Lowande, Kenneth S.
Abstract : Though considerable research focuses on formal institutions in Congress, scholars have long acknowledged that much of what guides legislative behavior is unwritten. To advance this area, we leverage a tool that allows appropriators to redirect billions of dollars from mandatory programs to discretionary projects. Changes in mandatory program spending—known as "CHIMPs"—show that existing institutions are often maintained by the strategic action of legislators. In the case of CHIMPs, we find their use is largely a response to formal constraints and that they are preserved through avoidance of minimum reform coalitions. This highlights that the legislative process—and budgetary outcomes in particular—cannot be understood without attention to procedures which remain "off the books."